New Zealand species of Steneotarsonemus Beer (Acari: Tarsonemidae) - Lin, Jian-Zhen; Zhang, Zhi-Qiang (Zootaxa, 2005)
New Zealand Steneotarsonemus (Acari: Tarsonemidae) comprises three species: Steneotarsonemus (Neosteneotarsonemus) ramus sp. nov. collected from Poa litorosa in Tagua Bay, Auckland Island; Steneotarsonemus (Mahunkacarus) mayae sp. nov. found under leaf sheaths and on flower panicles of Dracophyllum strictum Hook in Awakino; and Steneotarsonemus (Steneotarsonemus) spirifex (Marchal) collected from ryegrass and pasture soil in Palmerston North and The Glen. Keys to world species of Steneotarsonemus (Neosteneotarsonemus) and Steneotarsonemus (Mahunkacarus) are provided.